Democracy and violence: global debates and local challenges - Schwarzmantel, John J.; Kraetzschmar, Hendrik (Democratization Special Issues, 2013)
This book examines the impact of political violence on democracy and democratisation with original case-studies drawn from Latin America, Europe, the Middle East, Africa and Asia. This book was published as a special issue of Democratizations.